The Development Concept of Pupils Health Risks with Special Education Needs Visual Impairment through the Implementation of Individual Teaching Plans - Mohd Norazmi, Nordin; Madzlan, Abet; Hung Moi, Tang; Ezra Alfandy, M Duin; Doris, Maying (Islamic Azad University, 2024)
In addition to academics, personality aspects are also decisive in increasing the achievement of MBPK with hearing impairment in school. There are several studies that show that the personality aspect is an important aspect in giving statements related to the development of hearing impaired MBPK. Hearing-impaired MBPK who show high character can help them to learn effectively at school. This statement is in line with the earlier studies who think that personality can guarantee a quality event for hearing impaired MBPK. In addition, aspects of co-curricular development also affect student development. According to studies, student involvement in sports activities can develop students' physical, emotional, spiritual, intellectual and social talents. Student development in the extracurricular can also increase student self-confidence through involvement in sports competitions, games or uniformed bodies. The development of this co-curriculum is seen as very important in determining the future of students, including special needs students with hearing problems.